Acute effect of alternating heavy and light resistances on power output during upper-body complex power training - Baker, D. (The Journal of Strength and Conditioning Research, 2003)
This study investigated the effect on upper-body power output of manipulating resistances during contrast or complex power training. This power-training strategy typically entails the athlete alternating sets of a heavy resistance in a strength-oriented exercise with sets of lighter resistances in a power-oriented exercise. Sixteen rugby league players, who were experienced in power training and who performed complex training on a regular basis, served as subjects for this study and were divided equally into a control (Con) or experimental (Exp) group. Both groups were pre- and posttested for power output while performing explosive bench press throws in a Smith machine with a resistance of 50 kg (BT P50). The Exp group performed an intervention strategy of a 6-repetition set of bench presses with a resistance of 65% of 1 repetition maximum (65% 1RM) between tests. At the pretest occasion, no differences were observed between the groups in power output; however, at the posttesting, a significant difference in power output was observed between the groups in the BT P50. The 4.5% increase in the power output recorded during the posttesting BT P50 for the Exp group was determined to be significantly different from all other scores (p 0.05). These data indicate that the performance of a set of heavy resistance strength training exercise between power training sets will acutely enhance power output in the second power training set. This effect has been previously theorized as possibly due to some combination of acute neural or mechanical adaptations.